2022
DOI: 10.2147/jmdh.s382643
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Ferroptosis and Diseases

Abstract: Ferroptosis is an iron-dependent mode of cell death. It can occur through two major pathways, exogenous (or transporter-dependent) and endogenous (or enzyme-regulated) pathways are activated by biological or chemical inducers, and glutathione peroxidase activity is inhibited, which causes intracellular iron accumulation and lipid Peroxidation. Ferroptosis is closely related to the pathological process of many diseases. How to intervene in the occurrence and development of related diseases by regulating ferropt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 120 publications
0
12
0
Order By: Relevance
“…The Nrf2 pathway is a cellular defense mechanism that helps protect cells from oxidative stress by upregulating the expression of genes involved in antioxidant defense and detoxification. Vitamin K 2 has been shown to activate this pathway, leading to increased expression of antioxidant enzymes, including glutathione peroxidase [ 130 , 131 , 132 ]. Given the potential role of ferroptosis in COVID-19 pathogenesis and the possible link between vitamin K and ferroptosis, there is interest in exploring the potential therapeutic benefits of vitamin K in COVID-19.…”
Section: A Brief Overview Of Vitamin Kmentioning
confidence: 99%
“…The Nrf2 pathway is a cellular defense mechanism that helps protect cells from oxidative stress by upregulating the expression of genes involved in antioxidant defense and detoxification. Vitamin K 2 has been shown to activate this pathway, leading to increased expression of antioxidant enzymes, including glutathione peroxidase [ 130 , 131 , 132 ]. Given the potential role of ferroptosis in COVID-19 pathogenesis and the possible link between vitamin K and ferroptosis, there is interest in exploring the potential therapeutic benefits of vitamin K in COVID-19.…”
Section: A Brief Overview Of Vitamin Kmentioning
confidence: 99%
“…It has been reported that ferroptosis is frequently observed in I/R‐induced tissue injury (Lv et al, 2022). Compared with the Con group, lower expressions of GPX4 and SLC7A11 were detected in the Mod group (Figure 3f,g, p < .01).…”
Section: Resultsmentioning
confidence: 99%
“…In organs and tissues, in addition to oxidative stress and inflammatory cascading leading to cell autophagy, apoptosis, and necrosis, ferroptosis has been frequently reported in recent years to be implicated in the occurrence and development of I/R injuries (Li et al, 2021; Yan et al, 2020). Ferroptosis is a newly identified form of programmed cell death that is characterized by iron‐dependent accumulation of lipid peroxidation, during which excess generation of ROS promotes oxidative stress to damage organelles such as mitochondria, endoplasmic reticulum, and Golgi apparatus (Lv et al, 2022; Stockwell et al, 2017). Available evidence has shown that ferroptosis plays a role in enlarging I/R injuries and suppression of ferroptosis can mitigate various tissue damage caused by I/R in vivo (Chen et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…73 New research suggests that the heat shock protein β-1 (HSPB1) reduces intracellular iron content by inhibiting the expression of TFR1, thereby inhibiting ferroptosis. 63…”
Section: Ferroptosis Signaling Pathways In Asthmamentioning
confidence: 99%